COVID-19 Pandemic and Online Teaching: An Evidence from Universities of Pakistan - Tariq, Dr. Muhammad Arshad; Shah, Dr. Nazir Haider; Shaheen, Dr. Muhammad Naqeeb ul Khalil; Ahmed, Dr. Sadaf Zamir; Nabi, Dr. Ghulam; Jumani, Sakina (The journal of contemporary issues in business and government, 2021)
Owing to technological developments in artificial intelligence (AI), virtual reality (VR), augmented reality (AR), and cloud computing (CC), teaching at the university is moving from traditional to online sphere. This research article investigates how the university teachers teach students online across specific demographic variables. Through stratified sampling selection, 206 university teachers participated in the self-developed questionnaire survey. The reliability coefficient of the questionnaire was .91 by employing Cronbach’s alpha. t-test and ANOVAtechniques executed to analyze the data.It was found that the male university teachers than females, the sciences’ department than social sciences, the assistant professors than professors, and lecturers, and the university teachers with any teaching experience can teach students online. Continued research needs to conduct to analyze the university teachers’ intentions and attitudes towards online teaching adopting a standardizedsurvey Unified Theory of Acceptance and Use of Technology (UTAUT).